The Forsyte saga [videorecording (DVD)] - Wilson, Andy, 1958-; Lewis, Damian, 1971-; Graves, Rupert, 1963-; McKee, Gina, 1964-; Griffiths Malin, Emma, 1981-; Williams, Lee, 1974-; Galsworthy, John, 1867-1933 (Granada Television Ltd. ; Distributed by Acorn Media, 2003)
Set in the 1920s, two decades after the first series ends, the plot follows the courtship of two teenage Forsyte cousins: Fleur and Jon. Fleur, the daughter of Soames and Annette, and Jon, the son of Irene and Jolyon, meet by chance as youngsters; now Irene's son has fallen in love with the daughter of Soames, the man she despises above all others. Fleur and Jon haven't a clue that Soames and Irene were once married, all they know is that the family won't talk. Little do they suspect that their parent's dark secret will turn their nuptial dreams into a Romeo and Juliet ordeal.